(untitled) (Intent Research Scientific Journal, 2023)
The article describes the socio-psychological characteristics of creative thinking personality development in adolescence. Social psychological determinants of the formation of creative thinking skills are also classified. The components and results of experimental studies on the development of creative thinking in teenagers were analyzed